Analysis of the Role of Zakat Management Organizations in Empowering Mustahik in LazisMu and LazisNU - Amsari, Syahrul; Siregar, Saparuddin; Marliyah, Marliyah (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study is to analyze the role of zakat organizations in LazisMu and LazisNU in empowering mustahik. This research focuses on the two main zakat organizations in Indonesia, LazisMu and LazisNU, which come from Muhammadiyah and Nahdlatul Ulama. The role of LazisMu and LazisNU in managing zakat funds, distributing to mustahik, and implementing empowerment programs. This research uses a qualitative approach by using literature study as the main method. The results show that transparency and accountability in zakat management are essential to maintaining public trust. Zakat is not only responsible for managing and distributing funds, but also for bringing about social and economic change. There is evidence that LazisMu and LazisNU are actively implementing Mustahik empowerment programs. These programs include business capital, skills training, educational support, and health support. More than that, this research also found some problems such as transparency, accountability, and sustainability of the programs, although they are successful in various aspects. Therefore, this research provides a basis for exploring how zakat organizations can overcome these problems to achieve the goal of Mustahik empowerment. This research is expected to provide useful information for related parties, academics and practitioners in an effort to improve the role of zakat management organizations in helping disadvantaged people